PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI PERSAMAAN KUADRAT - Windawan, Rino Surya; Aziz, Muhammad Fail Abdullah; Khasanah, Mirsatun; Khasna, Ismi Nur Khaifa; ‘Izzati, Firsty Mustikaning Nur; Wijayanti, Dita Dwigus; Sagita, Laela (LP4MK STKIP PGRI Lubuklinggau, 2024)
This study aims to enhance students' mathematical problem-solving skills through the implementation of the Problem-Based Learning (PBL) model in the topic of quadratic equations. The research was conducted using the Classroom Action Research (CAR) method based on the Kemmis and McTaggart spiral model, consisting of two cycles with the stages of planning, action, observation, and reflection. The participants were 18 eleventh-grade students from a vocational high school (SMK) in Sleman. The findings revealed a significant improvement in students' mathematical problem-solving abilities, with the average score increasing from 75 in Cycle I to 84.72 in Cycle II. The PBL model proved effective in enhancing problem-solving skills. Challenges encountered during Cycle I, such as students' difficulties in understanding problems and lack of participation in group activities, were successfully addressed in Cycle II through improvements, including clearer visualizations in the Student Worksheets and more heterogeneous group arrangements. This study concludes that PBL is an effective teaching model for fostering meaningful learning and improving students' learning outcomes in the topic of quadratic equations.